Understanding Malaysian malays communication characteristics in reducing psychological impact on flood victims - Mustaffa C.S.; Marzuki N.A.; Khalid M.S.; Sakdan M.F.; Sipon S. (Universiti Kebangsaan Malaysia Press, 2024)
Indexed by WOS/SCOPUS